2003
DOI: 10.1149/1.1534098
|View full text |Cite
|
Sign up to set email alerts
|

A Theoretical Analysis of Brush Scrubbing Following Chemical Mechanical Polishing

Abstract: Wafer cleaning following chemical-mechanical planarization, especially brush scrubbing, is a critical step in semiconductor device manufacturing that is not adequately understood. A critical particle Reynolds number approach is used to assess whether hydrodynamic forces can remove adhering particles from wafer surfaces during brush scrubbing, or whether brush-particle contact must occur. Model systems of 0.1 and 1.0 m diameter alumina particles adhering to polished silicon dioxide and copper surfaces are consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 20 publications
0
18
0
Order By: Relevance
“…It is well known that etched copper surface is frequently contaminated by corrosion products, such as oxides, hydroxides, cuprous salts and Cu(1)-ions. The formation of cuprous oxides and/or hydroxides during copper exposure was detected in alkaline and peroxide containing solutions [27,79]. In chloride solutions (neutral and acidic) copper dissolution is accompanied by the formation of cuprous chloride (Cu(1)-Cl) [88,89].…”
Section: Solutions Chemical Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that etched copper surface is frequently contaminated by corrosion products, such as oxides, hydroxides, cuprous salts and Cu(1)-ions. The formation of cuprous oxides and/or hydroxides during copper exposure was detected in alkaline and peroxide containing solutions [27,79]. In chloride solutions (neutral and acidic) copper dissolution is accompanied by the formation of cuprous chloride (Cu(1)-Cl) [88,89].…”
Section: Solutions Chemical Compositionmentioning
confidence: 99%
“…Particle contamination of wafer surface occurring during polishing (emerging from pad material, or as suspended abrasive particles from various slurries, or from polished surface materials) is one of the major issues that should be taken into account subsequent to the CMP process. The amount of particles on the wafer surface is strongly dependent on CMP conditions, slurry type and hardness of the surface layer [78,79]. It is well known that particle contamination can occur due to adsorption process manifested by Van der Waals and/or electrostatic forces.…”
Section: Introductionmentioning
confidence: 99%
“…The average shear stress and the fluid film thickness are calculated using Eqs. (6) and (9), respectively, and they are plotted in Fig. 5.…”
Section: Resultsmentioning
confidence: 99%
“…4 By introducing a critical Reynolds number for particle removal, Burdick et al suggested that rolling is the dominant particle-removal mechanism during brush scrubbing and that the contact between a brush and a wafer is needed to remove particles. [5][6][7] Focusing on the adhesion and removal forces of a particle on a substrate during brush scrubbing, Busnaina et al found that full contact between a brush and a particle is necessary to lift or roll particles smaller than 0.1 m off a substrate. 8 However, until now, the removal mechanisms of nanosized particles during brush scrubbing have been far from clear, especially because no direct experimental data are available to backup the theoretical developments.…”
Section: Introductionmentioning
confidence: 99%
“…Improved understanding of how particles adhere to surfaces will enable optimal cleaning protocols to be developed so that less water and consumables can be used while still ensuring that all particles are removed from the surface. Predictions of the adhesion force between the particles and the wafer surface give the force that must be overcome to remove the particles, and can be used in cleaning models [1][2][3] to help optimize the wafer cleaning process.…”
Section: Introductionmentioning
confidence: 99%